A New Method for Evaluating Knowledge, Beliefs, and Neuromyths About the Mind and Brain Among Italian Teachers. Issue 2 (18th June 2020) - Tovazzi, Alice; Giovannini, Serena; Basso, Demis
ABSTRACT: Teachers often face situations that require them to apply knowledge about the mind and brain to education. Past studies have indicated that even if teachers show interest in cognitive neuroscience, they show high rates of adhesion to neuromyths. In the most commonly used questionnaire, however, respondents do not compare neuromyths and correct information based on neuroscience. The present study proposes a multiple‐choice questionnaire that presents scenarios occurring in school. The most commonly used and the new questionnaire were administered to 174 Italian teachers. In the most commonly used questionnaire, teachers generally had the same likelihood of accepting neuromyths as the literature reports. In the new questionnaire, the levels of both general knowledge and beliefs about neuromyths were significantly lower. Moreover, it suggests that teachers' adhesion to neuromyths in realistic situations does not match their explicit beliefs. Thus, the present research proposes that the use of questions based on feasible scenarios is a useful method to assess neuromyths.